Monostotic fibrous dysplasia of jaw bones: a case series - Alka Hande; Padmashri Kalmegh; Swati Patil; Archana Sonone; Aayushi Pakhale (BMC, 2024)
Abstract Background Fibrous dysplasia (FD) is a benign fibro-osseous lesion, a skeletal developmental anomaly of the bone-forming mesenchyme. The diagnosis of fibro-osseous lesions, particularly those of the jaw bones, poses significant challenges to clinicians and pathologists since it requires a correlation of clinical, radiological, histological, and surgical findings. Accurate and specific diagnosis is crucial as treatment modalities differ with different fibro-osseous lesions. Methods This retrospective analysis presents a case series of a rare condition of monostotic FD in the maxillofacial region affecting jaw bones diagnosed and/or treated over period of 10 years. Results Five cases of monostotic FD were diagnosed and treated between a period of 2013 and 2023. The cases from the 2nd to 8th decade were included in the analysis with equal involvement of males and females. Out of five cases, four cases were involving maxilla and 1 showed involvement of mandible. Conclusion FD is a rare entity affecting the jaw bones which often lead to disfigurement of face. Early detection is warranted to decrease potential complications. In addition, genetic analysis could help in understanding the occurrence in certain population.